Philosophical Approach in Legal Research - Wulakada, Al Ghozali Hide (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study discusses the philosophical approach in legal research as a fundamental framework that goes beyond the normative and empirical approaches commonly used in legal studies in Indonesia. This paper is motivated by the dominant tendency of the positivistic approach that ignores the philosophical dimension of law, thus making law merely a technocratic and functional instrument. This research is a normative legal research using a philosophical and conceptual approach. The philosophical approach is used to explore the ontological, epistemological, and axiological aspects of law, while the conceptual approach is used to examine key concepts such as the philosophical approach, legal epistemology, and legal rationality. In this study, the philosophical approach is approached through six forms: metaphysical, epistemological, ethical, logical, hermeneutical, and critical. Each approach is explained in a theoretical framework and its application in the context of legal research. The main findings show that the philosophical approach not only enriches theoretical insights, but also opens up reflective space to understand law as an expression of values, morality, and civility of society. Therefore, the integration of philosophical approaches in legal research methodology is very important in order to develop legal science that is not only normative and empirical, but also critical, ethical, and meaningful. This study also recommends the importance of reformulating legal education to be more sensitive to the philosophical and reflective dimensions, in order to produce graduates who are more critical and contributive to social transformation and legal science.